2018
DOI: 10.1111/bjhp.12316
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and parents of very young children: The role of beliefs and social‐cognitive factors

Abstract: This formative research provides further understanding of the factors that influence the PA behaviour of parents of very young children. Results provide targets for future interventions to increase PA for parents in a transition phase where PA levels decline. Statement of Contribution What is already known on this subject? Despite physical activity benefits, many parents are inactive following the birth of a child Social-cognitive models have demonstrated efficacy in predicting physical activity Weaknesses are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 73 publications
(118 reference statements)
1
3
1
Order By: Relevance
“…The current study found that action planning and coping planning did not have a mediating or moderating role in the behavioral intention - > ULFE-M pathway. It is inconsistent with previous researches ( Cowie et al, 2018 ; Lin et al, 2018 ). There may be two reasons for this: First, ULFE were strictly supervised by health care providers during the hospitalization of breast cancer patients after surgery.…”
Section: Discussioncontrasting
confidence: 91%
“…The current study found that action planning and coping planning did not have a mediating or moderating role in the behavioral intention - > ULFE-M pathway. It is inconsistent with previous researches ( Cowie et al, 2018 ; Lin et al, 2018 ). There may be two reasons for this: First, ULFE were strictly supervised by health care providers during the hospitalization of breast cancer patients after surgery.…”
Section: Discussioncontrasting
confidence: 91%
“…When other variables were entered in the equation predicting behaviour; however, it was action planning, and not intention, that emerged as the significant predictor of behaviour for three of the four self‐care behaviours and action planning was found to have a full mediational effect for the pathway between intention to behaviour. These findings highlight the importance of planning when, where and how to engage in self‐care and how it can facilitate the gap between behaviour intentions and engagement as predicted by the HAPA (Schwarzer, 2008) and is consistent with findings of the mediational role for planning in previous research on health behaviours, such as physical activity (Cowie, White, & Hamilton, 2018; Hamilton, Cox, & White, 2012). Planning may be particularly important for psychologists who have complex roles and are balancing multiple demands such as coursework (for trainees), clinical work and personal demands.…”
Section: Discussionsupporting
confidence: 87%
“…The necessity to better formalize the proposed “extended” models of the TPB has been advanced elsewhere (Rhodes, 2015). For example, some previous research has reported the relevance of considering the interplay between implicit and explicit processing components of self-control (Pfeffer & Strobach, 2017), whereas others have reported the interplay between some social resources (e.g., social support) and psychosocial variables (e.g., action planning) to enrich the TPB and enhance its predictive validity (Cowie, White, & Hamilton, 2018). The present study suggests to more routinely test and report interaction effects between the original TPB variables, and more systematically integrate and explore the interplay between some psychosocial and environmental variables when focusing on the processes involved the intentions–behavior relationship.…”
Section: Discussionmentioning
confidence: 99%